Misfortune or injustice?: The political work of postconflict narrative in contemporary Algeria - Mecellem, Jessica G. (International journal of transitional justice, 2018)
The Algerian regime has used a variety of stories to explain and refer to the conflict that occurred in the 1990s. This article explores these major narratives which were employed in regime discourse between 1996 and 2015. The article highlights the strategic use of language shifts between narratives identifying the violence as either ‘misfortune’ or as ‘injustice.’ The research presented here draws on analysis of a variety of primary source documents (government statements, official speeches at the domestic and international levels), in connection with fieldwork carried out by the author. The article highlights the dynamics associated with the two narratives, asking specifically what political work is being accomplished through the strategic use of regime narrative.